_silver fox_
silver n Suggested reserved [see 'auk' comment on draft] x Red fox., with a colour variation having black fur, etc. No because it is a red fox that isn't red OR x Red fox., with a colour variation_of black_ fur, etc. Since same definition is used for _silver_ & _silver_ hair entries, all 3 would [check] RH Used I and Sup Used I and Sup 2 Queried red fox, PATCH FOX Some text on back of card but it has been struck by the editors so I have not reproduced it.